NUTRITIVE EVALUATION OF GROWING YANKASA RAMS FED COWPEA SHELL BASED TOTAL MIXED RATIONS WITH DIFFERENT NITROGEN SOURCES - Matinja, U.I.; Abubakar, M.; Sani, I.; Bashir, Z.M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
An experiment involving sixteen (16) growing Yankasa rams was conducted to evaluate their feed intake, growth performance, rumen metabolites as well as blood profile when fed cowpea shell based total mixed rations with different nitrogen sources for 70 days Four diets were formulated as: 1(Urea/Maize offal), 2 (Sundried poultry litter/Maize offal), 3(Cotton seed cake/Maize offal) and 4(Groundnut cake/Maize offal). The results showed a significant (P<0.05) differences in daily weight gain (DWG), daily feed intake (DFI) and feed conversion ratio (FCR). The DWG was highest for treatment 2 (102.50 g/day) and lowest for treatment 3 (70.00 g/day). The results for DFI indicated a significantly higher value for treatment 4(842.04g/day) and lowest for treatment 3(521.23g/day). However, the results for FCR showed that treatment 2 recorded the best feed efficiency of 6.67 compared to others. The results for blood parameters indicated the following ranges: PCV (38.10 - 41.70%), haemoglobin (10.50 to 12.40 g/dL), white blood cells (8.90 to 12.50 x109/L), red blood cells (10.50 - 14.90 (10⁶/µL), mean corpuscular volume (25.57 - 36.09fl), blood glucose (3.20 - 3.90 mmol/L), blood urea (7.50 – 9.60 g/mmol) and total protein (56.40 - 76.50(g/L)) were all within normal values for healthy animals. The pH (Before and After) feeding (6.28 – 7.10 and 6.58 – 7.05) and Rumen ammonia nitrogen before (9.65-12.15mg/100ml) and after (19.15 - 22.38mg/100ml) feeding within recommended values for optimum rumen function. The levels of total VFA obtained in this study indicated higher values post-feeding (10.42 - 12.13). The high level of VFA post feeding of rams may have resulted from active digestion of fibre in the available residue. The results of the current study shows that growing Yankasa rams could be fed cowpea shell based total mixed rations with different nitrogen sources without any deleterious effects on the feed intake, growth performance, rumen metabolites as well as blood profile of the animals. In addition, animals on treatment 2 (Sundried poultry litter/ Maize offal) had the best average daily weight gains of 102.50g and the most feed efficiency of 6.67, therefore is recommended for growing Yankasa rams.